The Effect Of Learning Management System (LMS) Assistance In Think-Pair-Share Strategies On Learning Outcomes And Students Motivation Of Islamic State Senior High School - Ahmad Suhaili; Endang Budiasih; Surjani Wonorahardjo (Jurnal Pendidikan Sains, 2021)
Abstract: The purpose of this study was to determine the effect of Learning Management System (LMS) assistance in think-pair-share strategies and the effect of think-pair-share strategies on student learning outcomes and motivation. The research sample was 40 students of XI_A_1 and XI_A_2. The results showed that there were differences in learning outcomes and motivation between students who were taught with the Learning Management System (LMS) in the think-pair-share strategy and students who were taught with think-pair-share.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh bantuan Learning Management System (LMS) dalam strategi think-pair-share dan pengaruh startegi think-pair-share terhadap hasil belajar dan motivasi peserta didik. Sampel penelitian adalah 40 siswa XI_A_1 dan XI_A_2. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar dan motivasi antara peserta didik yang dibelajarkan dengan Learning Management System (LMS) dalam strategi think-pair-share dan peserta didik yang dibelajarkan dengan think-pair-share.